Assessment of Behavioral Characteristics With Procedures of Minimal Human Interference in the mdx Mouse Model for Duchenne Muscular Dystrophy - Engelbeen, Sarah; Aartsma-Rus, Annemieke; Koopmans, Bastijn; Loos, Maarten; van Putten, Maaike (Frontiers in Behavioral Neuroscience, 2021)
Duchenne muscular dystrophy (DMD) is a severe, progressive neuromuscular disorder caused by mutations in the DMD gene resulting in loss of functional dystrophin protein. The muscle dystrophin isoform is essential to protect muscles from contraction-induced damage. However, most dystrophin isoforms are expressed in the brain. In addition to progressive muscle weakness, many DMD patients therefore also exhibit intellectual and behavioral abnormalities. The most commonly used mouse model for DMD, the mdx mouse, lacks only the full-length dystrophin isoforms and has been extensively characterized for muscle pathology. In this study, we assessed behavioral effects of a lack of full-length dystrophins on spontaneous behavior, discrimination and reversal learning, anxiety and short-term spatial memory and compared performance between male and female mdx mice. In contrast to our previous study using only female mdx mice, we could not reproduce the earlier observed reversal learning deficit. However, we did notice small differences in the number of visits made during the Y-maze and dark-light box. Results indicate that it is advisable to establish standard operating procedures specific to behavioral testing in mdx mice to allow the detection of the subtle phenotypic differences and to eliminate inter and intra laboratory variance.